Designing of an Electric Light Sensor Circuit using Light Dependent Resistor for Auto Lighting Systems at Home. An experimental design - Ngonzi , Lawrance; Kamya, Willy (Student’s Journal of Health Research Africa, 2022)
Background : Due to the increasing wastage of electricity resulting from failure to switch off bulbs during day time, this research aimed at designing an electric light sensor circuit using a light-dependent resistor that helps to switch on and off lights at night and during the day respectively. The specific objectives was to generate an electric light sensor circuit using a light-dependent resistor and to determine the performance of an electric light sensor circuit in terms of resistance due to light exposure. Methodology: The research design was experimental; an electric light sensor circuit was designed and tested for its effectiveness. It was designed using resistors, a BC547 transistor, an LDR (Light dependent resistor), an led (bulb), and two resistors. Testing for the effectiveness of the electric light sensor was carried out based on Increasing the voltage on the DC power supply (from 2volts to 9volts) while reading the respective values of the resistance of the electric light sensor circuit using the multimeter and at the same time covering an LDR to create darkness on it. Results: A detailed analysis concerning the performance of the Electric light sensor system has been performed and presented. The device performed well using a light-dependent resistor as the light sensor. It was proven that the increase in the intensity of light falling on the light-dependent resistor as a light sensor makes the bulb (led) go off. This meant that during the day when the intensity of light was very high, the bulb (led) was off. Conclusion: A detailed analysis concerning the performance of the Electric light sensor system has been performed and presented. The device performed well using a light-dependent resistor as the light sensor. Recommendation: The system should next time be operated using the photocell instead of the LDR to improve its effectiveness.